Ελ Γκρέκο, Πικάσο και ο Αναλυτικός Κυβισμός - Markou, Georgios E. (My University, 2025)
This thesis investigates the artistic relationship between El Greco and Pablo Picasso, with a particular focus on the influence of El Greco on the development of Analytical Cubism. El Greco’s expressive distortion of forms, dramatic use of light and color, and spiritual dimension in his works served as a significant source of inspiration for Picasso. During his analytical cubist period, Picasso adopted techniques of fragmenting and reassembling forms, reflecting principles reminiscent of El Greco’s visual logic. The study includes a comparative analysis of selected works by both artists, highlighting parallels in the representation of the human figure, spatial conception, and compositional drama. It also examines the historical and artistic contexts that shaped Picasso’s work, exploring how the legacy of El Greco persisted and transformed within early 20th-century modern art movements. The dissertation aims to demonstrate the multidimensional connection between Renaissance tradition and modern art, emphasizing the aesthetic and theoretical bridge linking El Greco to Picasso through Analytical Cubism. It offers new insights into the evolution of contemporary visual expression and the enduring influence of past masters on avant-garde artistic innovation.
Keywords: El Greco; Picasso